New wave behaviors and stability analysis of the Gilson-Pickering equation in plasma physics - Ali, K. K.; Yilmazer, R.; Baskonus, H. M.; Bulut, H. (Indian Assoc Cultivation Science, 2021)
This study investigates the Gilson-Pickering equation by using the sine-Gordon expansion method. Sine-Gordon expansion method is one of the most powerful methods for solving the nonlinear partial differential equations. We successfully construct various exact solitary wave solutions to the governing equation, such as shock wave, topological, non-topological, compound topological, and non-topological soliton wave solutions. In addition, the stability of the studied nonlinear equation is analyzed via the linear stability analysis. The 2D, 3D, and contour surfaces are also plotted for all obtained solutions.
Keywords: The Gilson-Pickering equation; The sine-Gordon expansion method; Analytical wave solutions